Development of open-ended HOTS questions for elementary school students' creativity - Anjar Triyono; Subanji Subanji; Slamet Arifin (Inovasi Kurikulum, 2025)
This study aims to develop open-ended Higher-Order Thinking Skills (HOTS) questions to assess students' conceptual abilities in plane geometry. This development was carried out to provide assessment instruments following the curriculum and encourage creative problem solving. This research uses the research and development (R and D) method with the ADDIE model, which consists of five stages: analysis, design, construction, implementation, and evaluation. The research subjects were fourth-grade students of SDN Bareng 3 Malang. The research instruments included an expert report, a student survey for question validation, and an open-ended question analysis to measure the questions' validity, reliability, difficulty level, and differentiating power. Five open-ended questions related to pictures were used in this study. The results showed that the questions developed were valid. Thus, the open-ended HOTS questions can be used as valid and reliable assessment instruments and encourage student creativity in learning plane geometry.   Abstrak Penelitian ini bertujuan untuk mengembangkan soal-soal Higher-Order Thinking Skills (HOTS) terbuka guna menilai kemampuan konseptual siswa pada materi geometri bidang. Pengembangan ini dilakukan untuk menyediakan instrumen asesmen yang sesuai dengan kurikulum serta mendorong pemecahan masalah secara kreatif. Penelitian ini menggunakan metode penelitian dan pengembangan (R and D) dengan model ADDIE yang terdiri dari lima tahap: analisis, desain, konstruksi, implementasi, dan evaluasi. Subjek penelitian adalah siswa kelas IV SDN Bareng 3 Malang. Instrumen penelitian meliputi laporan ahli, survei siswa untuk validasi pertanyaan, dan analisis pertanyaan terbuka guna mengukur validitas, reliabilitas, tingkat kesulitan, serta daya pembeda soal. Lima pertanyaan terbuka terkait gambar digunakan dalam studi ini. Hasil penelitian menunjukkan bahwa soal-soal yang dikembangkan valid. Dengan demikian, soal-soal HOTS terbuka yang dikembangkan dapat digunakan sebagai instrumen penilaian yang valid dan reliabel serta mampu mendorong kreativitas siswa dalam pembelajaran geometri bidang. Kata Kunci: berpikir kreatif; open ended; pembelajaran matematika; soal HOTS